Surface Rotations on and Around a Semi-Parabolic Canyon in an Elastic Half-Space Induced by Out-of-Plane SH-Waves, I: Torsion. Issue 7 (3rd October 2017) - Lin, Chi-Hsin; Teng, Liping; Lee, Vincent W.
Abstract : The surface displacement amplitudes excited by out-of-plane SH waves on and around a semi-parabolic canyon had solution that was introduced over twenty years ago. In 2015, such solution was updated to much (5 times) higher frequencies, using a transformation involving the Wronskian. The same excitations also introduce rotations on and around the parabolic canyon. This article is the first of two that discuss the torsional component of rotations, with the rocking components discussed in the subsequent article. The rotational amplitudes of motions, as much as the displacement amplitudes, play an important role in studying the surface responses of structures, and can lead to a better understanding of the behavior of surface topographies in the event of seismic excitation.